Analisis Preferensi Konsumen Terhadap Sayuran Hidroponik Di Kota Sukabumi - Teti Febrianti; Asrul Tsani; Amalia Nur Milla (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2019)
There is society awerness in helat life style that makes consumer is more selective in choosing consumed vegetable. The hydroponic vegetable product that is free from pesticide becomes an alternative for consumer, which have health life style. The research aims at knowing how consumer preference toward hydroponic vegetable and knowing how consumer attitude toward a vegetable hydroponic attribute that is most consideration in a purchase decision. The research applied a descriptive method. Total respondents that were studied as much as 50 people by applying purposive sampling. Analysis design applied descriptive statistic and attitude analysis of fishbein multi-attribute. The resulting research declares consumer prefer hydroponic vegetable that has fresh level < 3 days, has a physical wide leaf which has no hole, different taste with conventional vegetable, type variety > 3 types, price < 5.000 IDR, and vegetable in the plastic package. The most consumer consideration attribute in purchase decision respectively is vegetable fresh level, leaf physic, package, vegetable taste, price, and type variety. The most vegetable type that is prefered by the consumer in pakcoy.